PENGARUH PERTUMBUHAN PERUSAHAAN, PROFITABILITAS, STRUKTUR ASET, RISIKO BISNIS, PAJAK DAN LIKUIDITAS TERHADAP KEPUTUSAN PENDANAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Nafisah, 13.05.52.0145; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2017)
This study aimed to analyze the influence of the companys growth, profitability, asset structure, business risk, tax and liquidity to funding decisions on manufacturing companies listed in Indonesia Stock Exchange. The population in this research is manufacturing companies listed in Indonesia Stock Exchange in 2013-2015. Sample selection is done by purposive sampling method. Data were processed as many as 242 companies. Mechanical testing data is by using multiple linear regression analysis. The results of analysis show that the variable tax and asset structure significant positive effect on funding decision, the variable growth of company and liquidity (current ratio) significant negative effect on funding decision, while the variable profitability (ROA) and business risk does not affect to the funding decision on Manufacturing companies listed on the Indonesia Stock Exchange.Keywords: Growth of Company, Profitability, Asset Structure, Business Risk, Tax, Liquidity and Funding Decision